Kesulitan Keuangan: Efek Struktur Kepemilikan, Karakteristik Dewan Direksi, dan Indeks Tata Kelola Perusahaan - Felix Williansyah; Meiliana Meiliana (Global Financial Accounting Journal, 2022)
Purpose – This study aims to examine the effect of the corporate governance on the firm financial distress. The independent variables consisted of ownership structure (managerial, foreign, institutional, family, and block holder’s), board characteristics (size, independent, educational background, meeting, and gender) and corporate governance index. Research Method – This study uses 168 sample companies selected by purposive sampling method. The hypotheses testing uses panel regression method. Findings – The result shows 116 of 168 sample companies (IDX) experienced financial distress. It has been proven that financial distress can be significantly reduced by increasing concentrated ownership and board education. In addition, foreign ownership and board size have a significant and positive impact on financial distress. However, managerial ownership, family ownership, institutional ownership, board independence, board meetings, board gender, and corporate governance index do not have an impact on financial distress. Implication – The findings of this study imply that financial distress occurs by the presence of foreign ownership because of rarely involved in company management. In addition, to avoid the risk of financial distress the company can be anticipated by improving the quality board of directors (education, expertise, CEO tenure) and strengthening the internal control.